Comparação dos resultados de ileostomias e colostomias em alça desfuncionalizantes em operações colorretais - Carmencita Marcatti Ferreira (2008)
Despite a lot of retrospective and prospective studies that compare loop ileostomy with loop colostomy controversy remains which technique has the best outcome on low colorectal anastomoses and function of the distal colon. The objective of this study is to describe complications and risk factors to complications after the construction and closure of loop ileostomias and colostomies. A retrospective analysis was completed of 168 patients who underwent loop stoma surgery between January 1996 and December 2006. Ileostomy was constructed in 88 patients (52,4%) and colostomy in 80 patients (47,6%). Complications after construction and closure and possible risk factors of these complications were assessed. The variables assessed were: age, gender, the base disease, ASA classification, temporary or definitive stoma, elective or emergency surgery, general or coloproctologist surgeon, post surgery complications, reoperations post construction, kind of closure, time until the closure and the time of follow-up after closure. The average age of ileostomy patients was bigger that colostomy patients (p=0,005). The majority of the colostomies was constructed on urgency (p<0,001) and the ileostomias on elective surgeries. Was found more temporary ileostomias then colostomies (p<0,001). The coloproctologist made the largest part of the ileostomies (p<0,001). The overall rate of stoma complications was 38,7%. No difference was found between the two operation techniques (p=0.334). Most common complication was stoma prolaps (19,6%). Prolaps occurred in 33,8% of the colostomies and in 6,8% of the ileostomies (p<0,001). Electrolyte disorders related to enteric loss were diagnosed in 11 patients (12,5%) in the ileostomy group and two cases (2,5%) in the colostomy group (p=0.019). One patient (0,6%) died in the colostomy group and was related to complications of stoma. The majority of stoma related complications occured in women (p=0.024) and in that women with a colostomy (0,045). No difference was found in complication rate between elective and emergency surgery. The general complication rate after closure was 47,7% and, without differences between the complication rate between ileostomy and colostomy (p=0,670). The most frequent closure complication was wound infection (20,6%). With this results was found that general complication rate between loop ileostomies and colostomies are comparable. When we value the complications apart, we can note that the complication more frequent in patients with colostomy, stoma prolaps was more serious and resulted in reoperation, whereas, on ileostomies the electrolyte disorders were managed with clinic treatment. The interpretation of the results, suggest that ileostomy is better option when compared with colostomy, to deviate the transit of gut.